1985
DOI: 10.1177/019262338501300410
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Phospholipidosis Induced by an Amphiphilic Cationic Psychotropic Drug

Abstract: Numerous amphiphilic cationic drugs cause generalized phospholipidosis in animals; one of these drugs is the Sandoz compound 200-125, a psychotropic agent. During a 6-month toxicity study in Charles River CD rats, a dramatic increase in foamy macrophages was seen in the lungs. A follow-up experiment was done to study the pathologic basis of these changes including a reversibility phase. Generalized phospholipidosis was induced after 4 weeks of 500 mg/kg/ day of 200-125 by gavage. Characteristic pulmonary lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…Drogas catiônicas anfifílicas têm sido responsabilizadas por induzirem à fosfolipidose, um acúmulo intracelular excessivo de fosfolipídeos, que pode ocorrer em qualquer tecido do corpo, mas, principalmente, na língua, fígado, rim, tecido ocular, coração, adrenal, tecido hematopoético e linfócitos circulantes. Ainda não foi possível definir o mecanismo exato da fosfolipidose induzida por drogas (Robison et al 1985). Até o momento não foram realizadas avaliações lectino-histoquímica dessas células.…”
Section: Discussionunclassified
“…Drogas catiônicas anfifílicas têm sido responsabilizadas por induzirem à fosfolipidose, um acúmulo intracelular excessivo de fosfolipídeos, que pode ocorrer em qualquer tecido do corpo, mas, principalmente, na língua, fígado, rim, tecido ocular, coração, adrenal, tecido hematopoético e linfócitos circulantes. Ainda não foi possível definir o mecanismo exato da fosfolipidose induzida por drogas (Robison et al 1985). Até o momento não foram realizadas avaliações lectino-histoquímica dessas células.…”
Section: Discussionunclassified
“…At the time of the publication, however, it was not recognized that the response was a PLDsis because this phenomenon was unknown. Subsequent research has confirmed that the foamy macrophages develop as a result of the accumulation of phospholipids within the cell and are a common response to so-called cationic amphiphilic drugs (CADs) 5,6 . Since that time, over 50 marketed and experimental CADs have been reported to induce PLDsis following in vitro and in vivo administration and/or under ex vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
“…9 Reactions were magnetically stirred and were run under an atmosphere of N 2 . 1 H, 13 C, and 31 P NMR spectra were acquired on a Bruker Avance I spectrometer running at a proton frequency of 500.1 MHz, and chemical shifts are reported in ppm (δ) relative to tetramethylsilane or the residual solvent resonance (7.26 and 77.16 ppm for CDCl 3 ). Flash column chromatography was carried out using prepacked silica gel columns supplied by Biotage and using a Biotage automated flash system with UV detection.…”
Section: Discussionmentioning
confidence: 99%